MUSHROOM MODELS AS A MEANS OF LEARNING - García García, Manuel Antonio; Cappello García, Silvia (Kuxulkab', 2023)
Handmade three-dimensional models are an essential learning tool for students at any educational level. For the undergraduate students in biology at the Academic Division of Biological Sciences, the use of these elements has been very useful, where imagination and creativity are reflected in the beauty of many specimens. During the fabrication of the fungi models the student acquires general and specific knowledge about the fungi kingdom, can easily recognize the typical structures that define these organisms, and discern between the various groups found in the fungi kingdom. In general, the paper describes the importance of the fungal models handmade by biology students and the outreach they generate inside and outside the classroom.
Keywords: Collection; Fungal exposure; Social knowledge; Skills